Sistem Kontrol pada Automated Guided Vehicle Beroda Mekanum menggunakan Sliding Mode Controller - Muhammad Faiz; Bambang Sumantri; Bima Sena Bayu Dewantara (Universitas Syiah Kuala, 2023)
The production in industry, are involving distribution to transport the goods. Recently, distribution activities are using unmanned vehicle, that is Automated Guided Vehicle (AGV). In real condition, AGV are facing environment with complexity of high uncertainity and unlinearity. Because of this, robust control method could be considered to be used to improve the control performance. For instance, Sliding Mode Control has good robustness to the uncertainity of the system and disturbances. However, the chattering phenomenon is one of the major issues of the sliding mode control. This phenomenon could damage the motor. This research aim to reduce chattering and improve the control performance, with modifying signum function to saturation function. This research are using ROS, V-Rep and microcontroller. Microcontroller for processing algorithm and another function. Moreover, saturation function had succcessfully reducing rise time about 30%, overshoot 16% and RMSE 0.21%.